Vale de lágrimas: um estudo a respeito da noção de doença sob o ponto de vista de religiões brasileiras no início do século XXI - Silva, Glayton Alexandre da (2009)
This study intends to analyze the interpretation of sickness among Brazilian religions. Based upon the theory of Social Representations it will be identified the interpretations of sickness causality according to catholics, protestants, spiritists and Afro-Brazilian religion followers (umbanda and candomblé). In order to accomplish such purpose it is first suggested a discussion to better define controversial terms such as sickness and religion, as well as the relationship between the latter and medical practice. Etiologic models and popular conceptions of sickness reveal the importance of comprehending health/sickness representations as they work as a measure to social behaviors such as protection, exclusion and aiding of sick people. The history of health/sickness representations was always ruled by the inter-relationship of human beings and their bodies with several natural, social and supernatural elements. Due to the therapeutic role played by religions during centuries, religion believes pervade these representations and they inevitably led to the moralization of diseases. This evidence shows that when it comes to social representation of sickness the more things change the more they remain the same. Disease moralization process and the promotion of health to the status of "social ideal" by modern medicine and by religions as a whole have influenced the way social agents affected by disease, as well as the religious group they belong to, used to face suffering. Inquiries concerning the reason of the diseases have moved from how? to why? and the disease first conceived as a mere physiologic change in the human body has its domains extended far beyond it